Neuromuscular Excitation Pattern in Expert Indoor Skydivers - Susanna Rampichini; Eloisa Limonta; Irene Di Giulio; Marta Borrelli; Emiliano Cè; Giuseppe Coratella; Johnny Padulo; Stefano Longo; Fabio Esposito (Applied Sciences)
The evolution of indoor skydiving from military origins to a globally recreational pursuit has attracted individuals without prior specific training, exposing them to the heightened risk of muscle–joint injuries associated with indoor skydiving. This study aims to assess the muscular excitation patterns in highly skilled instructors to determine the optimal activation strategies for preventing musculoskeletal injuries. Nine expert indoor skydiving instructors (M/F: 8/1; age 31 ± 7 years; body mass: 70.5 ± 11.1 kg; stature: 1.74 ± 0.09 m) were enrolled. The surface electromyographic signal was recorded on the anterior deltoid, AD; posterior deltoid, PD; pectoralis major, PM; latissimus dorsi, LD; rectus abdominis, Rabd; erector spinae, ES; rectus femoris, RF; and biceps femoris, BF for each position: PRONE, SUPINE, SIT, and head-down (HD). A synchronous heart rate was recorded to assess the cardiac engagement. The neuromuscular load (NeLo), representative of the excitation amplitude of a muscle set, was determined for each position across different body regions. PRONE and SUPINE were the least demanding in terms of cardiac engagement (67 ± 6 and 85 ± 8 bpm, respectively) and exhibited the lowest neuromuscular excitation (24 ± 10 and 24 ± 8% Max, respectively). By contrast, HD exhibited the highest cardiac (127 + 18 bpm) and neuromuscular (71 + 11% Max) engagement and particularly in the lower-trunk and lower-limbs muscles. SIT predominantly engaged upper-trunk and shoulder muscles. The findings indicate the significant engagement of the musculature surrounding the shoulder joint and that responsible for lower-trunk stabilization in maintaining the investigated positions. A targeted training regimen on strengthening these muscles is advised before practicing indoor skydiving to prevent shoulder joint injuries or lower back muscle overloads.